A produção de sentidos do discurso bolsonarista sob a perspectiva de Bakhtin e Rosenfeld: uma análise do discurso sobre a fragmentação da alteridade, a deslegitimação dos direitos humanos, a polarização político-ideológica e a erosão da democracia - Azevedo, Silvagner Andrade de (2025)
This thesis investigates how the meanings produced by Jair Bolsonaro’s discourse throughout his political trajectory challenge the foundations of the Democratic Rule of Law and compromise democracy, the realization of fundamental rights, and the construction of the identity of the constitutional subject in Brazil. As a provisional response to this issue, the hypothesis is raised that Bolsonarist discourse generates meanings that threaten fundamental rights, fragment alterity, reinforce political and ideological polarization, and contribute to the erosion of democracy. These meanings shape a homogeneous and exclusionary identity of the constitutional subject, contradicting the principles of plurality, equality, and human dignity enshrined in the 1988 Federal Constitution. Situated within the research domain of Democracy, Citizenship, and Fundamental Rights, this study aims to analyze, through the theoretical lenses of Bakhtin and Rosenfeld, how Bolsonaro’s speeches constitute a discourse whose meanings challenge constitutional principles, hinder the realization of fundamental rights, and weaken democracy. Based on Mikhail Bakhtin’s dialogic theory of language, the study examines the meanings produced by Bolsonaro’s speeches, categorized into four analytical dimensions: delegitimization of human rights, fragmentation of alterity, political and ideological polarization, and democratic erosion. These meanings not only undermine the pillars of democracy but also foster the exclusion and stigmatization of socially vulnerable groups, thereby threatening the effective protection of fundamental rights. From the perspective of Michel Rosenfeld’s constitutional theory, the study further explores the tension between the meanings produced by Bolsonarist discourse and the constitutional-legal discourse, highlighting how these narratives jeopardize the construction of a plural and inclusive constitutional subject. Methodologically, this thesis constitutes an explanatory, qualitative, and transdisciplinary investigation that combines theoretical analysis—grounded in language theory and constitutional theory—and discourse analysis to understand the effects of Bolsonarist discourse in shaping an exclusionary political environment that challenges constitutional discourse. For the organization and systematization of the corpus composed of Bolsonaro’s speeches, the study employs content analysis based on Bardin’s methodology. The research adopts the dialectical method as its scientific approach, applying it to the analysis of Bolsonaro’s discourse to identify how his statements reflect and challenge contradictions within Brazilian society, such as the tension between inclusion/exclusion or authoritarianism/democracy. As a result—and confirming the initial hypothesis—the study demonstrates that Bolsonarist discourse, when analyzed through the selected theoretical framework, produces meanings that conflict with the constitutional text and undermine fundamental rights and democracy. Bolsonaro’s discourse repeatedly delegitimizes human rights, excludes and stigmatizes marginalized groups, promotes political and ideological polarization, and weakens democracy, while simultaneously constructing a homogeneous and exclusionary identity of the constitutional subject. The thesis concludes that political language, as a space for meaning-making, has the power to reshape the social and institutional imaginary, thereby weakening the foundations of democracy and constitutional principles. The research underscores the need for a critical understanding of constitutional jurisdiction and democracy in the face of discourses that threaten the pillars of the Democratic Rule of Law